Factor structure of coping strategies and their relationship with the parameters of self-regulation styles athletes and Paralympians - Shestilovskaya, Natalia A. (Journal of the Belarusian State University. Philosophy and Psychology, 2021)
High physical and psychological loads in sports often lead to stress. The possibility of performing sports activities and resisting the action of stress factors in the event of various difficult situations is realised through coping strategies, ensuring the effectiveness of self-regulation. This article presents the results of a factor analysis of the coping strategies of athletes and paralympians, and their comparison, and the results of studying relationships between coping strategies and parameters of self-regulation styles.